Thermally induced cracking on the massive concrete structure of the NSLS II synchrotron and its engineering remediation. (1st June 2020) - Simos, N.; Fallier, M.; Joos, T.; Johnson, E.; Soueid, Ahmad
Highlights: Thermally Induced Cracking of Concrete Structure of the NSLS II Synchrotron and its Remediation. Achieving nm-level stability in a next generator synchrotron accelerator with "monolithic" design and continuous steel rebar. Deviation from monolithic design combined with extreme ambient temperature fluctuations, led to cracking threatening stability performance. 3D non-linear FEM precisely reproduced the cracking behavior of the massive structure and identified optimal remediation solution. Implementation of the numerically identified solution for crack arrest successfully halted crack progression meeting stability requirements. Abstract: Synchrotron accelerator facilities such as the NSLS II require extreme stability, both transient (short-term) and quasi-static (long-term) to achieve the desired resolution performance. Consequently, even μm-level movements, particularly differential movements between locations in the concrete structure supporting the accelerator electron beam lattice (storage ring) or high sensitivity experiments (experimental floor) will lead to serious degradation of its performance. Differential settlement in the overall structure or structural movement exceeding anticipated levels will inevitably degrade the performance and will require intervention. Presented in this paper are the design philosophy of the NSLS II ring structure favoring a monolithic ring, the observed cracking behavior of the young NSLS II concrete following casting and in combination with extreme ambient temperature fluctuation, the results of a non-linear, high-fidelity numerical analysis used to emulate the observed cracking and establish the driving mechanism, the numerical analysis-based identification of the crack-arresting solution and finally the implementation of the remediation solution and the long-term performance of the adopted engineering solution. The multi-stage process revealed that computational methods such as non-linear finite element methods have the potential of providing engineering guidance even when complex structures and in combination with non-linear materials, such as steel reinforcement and concrete are involved.